2006
DOI: 10.1074/jbc.m512449200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Murine TGFβ2 by Pax3 during Early Embryonic Development

Abstract: Pax3 encodes a paired homeobox containing transcription factor that is expressed in neuroepithelium, neural crest, and presomitic mesoderm (1). Homozygous mouse embryos carrying a loss-of-function Pax3 allele (Pax3 Ϫ/Ϫ ) develop open neural tube defects, such as exencephaly or spina bifida (2), and die around embryonic day 14 (E14) 4 as a consequence of heart defects (3). More recently, Pax3 has been shown to function at the nodal point in melanocyte stem cell differentiation (4). Heterozygous embryos (Pax3 ϩ/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 43 publications
0
33
1
Order By: Relevance
“…Therefore, which enzyme functions as an upstream deacetylase remains to be a critical question. It has been shown that HDAC10 interacts with HDAC2 and HDAC3 (5,8), and one recent report showed that HDAC1 coimmunoprecipitates with acetylated Pax3 in a medulloblastoma cell line with stably transfected Pax3 (32). However, in our laboratory we observed that Pax3 failed to interact with HDAC1, HDAC2, HDAC3, or HDAC8 in coimmunoprecipitation experiments.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Therefore, which enzyme functions as an upstream deacetylase remains to be a critical question. It has been shown that HDAC10 interacts with HDAC2 and HDAC3 (5,8), and one recent report showed that HDAC1 coimmunoprecipitates with acetylated Pax3 in a medulloblastoma cell line with stably transfected Pax3 (32). However, in our laboratory we observed that Pax3 failed to interact with HDAC1, HDAC2, HDAC3, or HDAC8 in coimmunoprecipitation experiments.…”
Section: Discussioncontrasting
confidence: 54%
“…Nevertheless, we do not exclude the possibility that other HDACs also participate in the modulation of the activities of proteins targeted by HDAC10. In fact, Mayanil et al (32) showed that SirT1 binds to transforming growth factor-␤ promoter fragments where Pax3 binds, suggesting that SirT1 or other NAD ϩ -dependent HDACs might participate in HDAC10-mediated regulatory events as upstream deacetylases of target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo assays performed during mouse embryonic development show that Pax7 targets a complex array of receptors and intracellular signaling pathways, including integral components of Ras-MAPK, JAK-STAT, and calmodulin-dependent signaling pathways (White and Ziman, 2008). Importantly, this echoes multiple studies implicating Pax3 in the regulation of receptors and components of signaling pathways such as the secretory glycoprotein Wnt1 (Fenby et al, 2008), HGF / c-Met (Epstein et al, 1996;Mayanil et al, 2001;Relaix et al, 2004;Tomescu et al, 2004), c-RET (Lang et al, 2000;Lang and Epstein, 2003), as well as both TGF-␣ (Barber et al, 2002) and TGF-␤2 (Mayanil et al, 2006). Multiple isoforms of Pax3 are also known to independently regulate signaling and morphogen response pathways by means of the Shh functional homologue Dhh, Fgf17, Kitl, and Rac1 to control cell differentiation and proliferation (Wang et al, 2007).…”
Section: Pax Downstream Targetsmentioning
confidence: 84%
“…Work from our lab established a link between Pax3 and TGFβ2 (Mayanil et al, 2006). Pax3 regulates the TGFβ2 promoter by binding to its cis-regulatory elements, and TGFβ2 expression is diminished in Pax3 -/-embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Pax3 regulates the TGFβ2 promoter by binding to its cis-regulatory elements, and TGFβ2 expression is diminished in Pax3 -/-embryos. Thus a regulatory relationship exists between Pax3 and TGFβ2 (Mayanil et al, 2006).…”
Section: Introductionmentioning
confidence: 99%